Evaluation of in vitro human skin models for studying effects of external stressors and stimuli and developing treatment modalities. Issue 2 (15th September 2021) - Sutterby, Emily; Thurgood, Peter; Baratchi, Sara; Khoshmanesh, Khashayar; Pirogova, Elena
Abstract: Skin is exposed to a variety of potential stressors and stimulators that may impact homeostasis, healing, tumor development, inflammation, and irritation. As such it is important to understand the impact that these stimuli have on skin health and function, and to develop therapeutic interventions. Animal experiments have been the gold standard for testing the safety and efficacy of therapeutics and observing disease pathology for centuries. However, complex ethics, costs, time consumption, and interspecies variation limit the transferability of results to humans and reduce their repeatability and reliability. Furthermore, traditional 2D cell studies are not representative of human tissue. Skin tissue is a dynamic environment, and when cells are isolated in unphysiologically stiff, static petri dishes their behavior, and phenotypic expression is altered. Increasingly complex in vitro models of human skin, including organoids, 3D bioprinting, and skin‐on‐a‐chip platforms, present the opportunity to gain insight into how stressors affect tissue at a cellular level in a controlled and repeatable environment. This insight can be leveraged to further understand pathological skin conditions and better formulate and validate drugs and therapeutics. Here, we will discuss the application of in vitro skin modeling to investigating the effects of mechanical, electromagnetic, and chemical stressors on skin. Abstract : Skin acts as an interface between ourselves and our external environment. Consequently, our skin must interact with a variety of potential stressors while retaining homeostatic balance. Increasingly complex models of human skin are being developed, including organoids and skin‐on‐chip platforms, that offer increased physiological relevance. The present review collates the application of different in vitro models of human skin to investigating the impact of mechanical, electromagnetic, and chemical stressors. It also highlights advantages, limitations, and future avenues for advancements of in vitro skin models.